Merenungkan Kembali Pertanyaan "Siapakah Sesamaku Manusia?" : Sebuah Pengantar Editorial - Adrianus Yosia (Indonesian Journal of Theology, 2020)
This is an editor introduction to the special issue Rethinking the Idea of "Who is My Neighbor?"